Tratamento cirúrgico de ameloblastoma mandibular - Jardim, Ellen Cristina Gaetti; Faverani, Leonardo Peres [UNESP]; Melo, Rosana Leite de; Miyahara, Glauco Issamu [UNESP]; Soubhia, Ana Maria Pires [UNESP]; Mendonça, José Carlos Garcia de; Shinohara, Elio Hitoshi [UNESP] (My University, 2013)
Ameloblastomas are benign, invasive locally and highly recurrent. It is an odontogenic tumor, characterized by the proliferation of epithelial ameloblastic in a fibrous stroma. This paper reports a case of mandibular ameloblastoma, in patients 27 years of age without pain with developments around 4 years, with about 20 mm at its greatest extent, sessile base and surface coatings full. The treatment of choice was the surgical conservative

Ameloblastomas son benignos, localmente invasivo y altamente recurrente. Se trata de un tumor odontogénico caracterizado por la proliferación de epitelio ameloblástico en un estroma fibroso. En este trabajo se reporta un caso de ameloblastoma mandibular en un paciente de 27 años de edad sin quejas de dolor, un aumento de cerca de cuatro años, con cerca de 20 mm en su mayor medida, la base sésil y revestimiento de la superficie intacta. El tratamiento de elección es la cirugía conservadora.

Ameloblastomas são tumores benignos, localmente invasivos e altamente recidivante. É um tumor odontogênico, caracterizado pela proliferação do epitélio ameloblástico em um estroma fibroso. O presente trabalho relata um caso de ameloblastoma mandibular, em paciente de 27 anos de idade sem queixas álgicas, com evolução de cerca de 4 anos, com cerca de 20 mm em sua maior extensão, base séssil e superfície de recobrimento íntegra. O tratamento de escolha foi o cirúrgico conservador.
Surgical treatment of mandibular ameloblastoma
Tratamiento quirúrgico de ameloblastoma mandibular
Keywords: Pathology oral; Oral medicine; Ameloblastoma; Patología bucal; Diagnóstico bucal; Ameloblastoma; Tumores odontogênicos; Cirurgia bucomaxilofacial